Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Find reliable answers to your questions from a wide community of knowledgeable experts on our user-friendly Q&A platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
2x - 3y = 6
-3y = 6 - 2x
y = (6-2x)/(-3)
y = 6/-3 - 2x / -3
y = -2 + (2/3)x
Explaination :
Given equation,
- 2x - 3y = 6
Our aim is to solve the given equation and get out the value of y.
Transposing the 2x which is in L.H.S. to R.H.S.,
[tex]\implies \: \displaystyle{ \sf{2x - 3y = 6}} \\ \\ \implies \: \displaystyle{ \sf{- 3y \: = \: 6 - 2x}} \\ \\ \implies \: \displaystyle{ \sf{3y \: = \: 2x - 6}}[/tex]
Dividing the R.H.S. with 3,
[tex]\implies \: \displaystyle{\sf{y \: = \: \dfrac{2x - 6}{3}}} \\ \\ \implies \: \displaystyle{ \red{\bf{y \: = \: \dfrac{2x}{3} \: - \: \dfrac{6}{3} }}}[/tex]
We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.